2015
DOI: 10.1093/eurheartj/ehv008
|View full text |Cite
|
Sign up to set email alerts
|

Screening for dysglycaemia in patients with coronary artery disease as reflected by fasting glucose, oral glucose tolerance test, and HbA1c: a report from EUROASPIRE IV—a survey from the European Society of Cardiology

Abstract: In patients with established coronary artery disease, the OGTT identifies the largest number of patients with previously undiagnosed diabetes and should be the preferred test when assessing the glycaemic state of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 44 publications
2
68
0
3
Order By: Relevance
“…25 These studies did not include a population of patients with verified CAD. The recent report from EUROASPIRE IV demonstrated that screening coronary patients with HbA1c, and FPG alone left one in five patients with undetected DM 9. Yet, this combination alone has been advocated as sufficient for diagnosing DM in patients with CAD 26…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 These studies did not include a population of patients with verified CAD. The recent report from EUROASPIRE IV demonstrated that screening coronary patients with HbA1c, and FPG alone left one in five patients with undetected DM 9. Yet, this combination alone has been advocated as sufficient for diagnosing DM in patients with CAD 26…”
Section: Discussionmentioning
confidence: 99%
“…Details of EUROASPIRE IV, conducted in 24 European countries from May 2012 to April 2013, have been presented elsewhere 9. This description relates to details of special interest for the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During ORIGINALE, incident diabetes was diagnosed by means of the HbA 1c level, which is a less sensitive test than the oral glucose tolerance test used in ORIGIN (11). Nevertheless, when incident cases of confirmed diabetes that developed during ORIGINALE (after insulin was discontinued for all participants without diabetes at the end of the trial) were added to those identified during ORIGIN, there was a consistent (albeit nonsignificant) 5% reduction in newly developed diabetes that achieved significance when 69 possible but unconfirmed cases of diabetes were added.…”
Section: Discussionmentioning
confidence: 99%
“…Oral glukosetoleransetest er i noen studier vist å ha prognostisk verdi og kan vurderes etter en akutt koronar hendelse, men anbefales ikke som fast rutine (13,14,(16)(17)(18).…”
Section: Diskusjonunclassified